A New Heterometallic Silver/Cadmium Thiocyanate Directed by Benzyl Viologen Possessing Photocurrent Response and Photocatalytic Degradation on Rhodamine B in Artificial Seawater - Xueqiang Zhuang; Xihe Huang; Haohong Li; Tianjin Lin; Yali Gao (Crystals)
The search for new heterometallic metal pseudohalides will be significant for the development of novel functional materials. In this work, a new silver/cadmium heterometallic thiocyanate templated by benzyl viologen has been synthesized and structurally determined, i.e., {(BV)[Ag2Cd(SCN)6]}n (BV2+ = benzyl viologen). The interesting 1-D double chain [Ag2Cd(SCN)6]n2n− was constructed from the CdN6 octahedron and Ag2SCN6 dimers via μ2-SCN and μ3-S,S N SCN bridge, in which the Ag···Ag interaction can be found. Inter-molecular C-H···S/N hydrogen bonds between BV2+ cations and [Ag2Cd(SCN)6]n2n− chains contribute to the formation of a stable 3-D network. The short S···N distance implies the strong charge transfer (CT) interactions between the electron-rich silver/cadmium thiocyanate donor and BV2+ acceptor. This hybrid can exhibit a photo-generated current performance with an intensity of 1.75 × 10−8 A. Interestingly, this hybrid can present good photocatalytic degradation performance on rhodamine B in artificial seawater with a degradation ratio of 86.5% in 240 min. This work provides a new catalyst way for the organic dye-type ocean pollutant treatments.